2020
DOI: 10.1111/bph.15247
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tuberculosis effect of isoniazid scales accurately from zebrafish to humans

Abstract: What is already known  The zebrafish is a well-known tuberculosis disease model for qualitative efficacy screens in drug development.  The information content and translational potential of qualitative assessments is low. What this study adds  The isoniazid exposure-response relationship is quantified in zebrafish larvae using integrated experimental and computational innovation.  With pharmacokinetic-pharmacodynamic modelling, quantitative translation of pharmacological findings from zebrafish larvae to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recently, a proof-of-concept study from van Wijk et al (2020b) showed that the isoniazid concentration in blood was only 20% of the external drug concentration. Using pharmacokinetic-pharmacodynamic modeling, the authors described the exposure-response relationship and concluded that the early bactericidal effect of isoniazid in human infections translates to the responses observed in the zebrafish model ( van Wijk et al, 2020b ). A similar study was performed on paracetamol, showing that blood concentrations in the embryo were only 10% of the external paracetamol concentration in the fish water ( Van Wijk et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a proof-of-concept study from van Wijk et al (2020b) showed that the isoniazid concentration in blood was only 20% of the external drug concentration. Using pharmacokinetic-pharmacodynamic modeling, the authors described the exposure-response relationship and concluded that the early bactericidal effect of isoniazid in human infections translates to the responses observed in the zebrafish model ( van Wijk et al, 2020b ). A similar study was performed on paracetamol, showing that blood concentrations in the embryo were only 10% of the external paracetamol concentration in the fish water ( Van Wijk et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…This was recently illustrated in the field of tuberculosis, a disease that is studied in zebrafish larvae infected with M. marinum, a close relative of the human pathogen M. tuberculosis. By correcting for differences in drug sensitivity between the two bacterial species and differences in the growth phase of the bacterial infections in larvae and humans, findings in zebrafish larvae on the efficacy of isoniazid were successfully translated to humans [120]. Similar approaches could be applied in the research on neonatal sepsis to overcome potential issues arising from differences in maturation and function of immunological cell types or signaling pathways, or from differences in body temperature.…”
Section: Future Perspectivesmentioning
confidence: 99%